2002
DOI: 10.1063/1.1489484
|View full text |Cite
|
Sign up to set email alerts
|

Height-controlled InAs quantum dots by using a thin InGaAs layer

Abstract: The structural and optical properties of height-controlled InAs quantum dots (QDs) have been investigated by transmission electron microscopy (TEM) and photoluminescence (PL). By depositing 1.4 nm In0.15Ga0.85As and a 1 monolayer (ML) InAs layer with different periods on 3 ML InAs QDs, the height of InAs QDs was systematically controlled with similar lateral size. In TEM images, the indication of dislocations due to the large strain, which can be easily seen in large QDs, is not observed even for the QD sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The luminescence light from the sample was focused with collection lenses, dispersed by a 1.2 m SPEX single grating monochromator and detected by a liquid nitrogen cooled Ge detector. InAlAs have elongated-shape along the [1][2][3][4][5][6][7][8][9][10] direction. This can be attributed to intrinsic InAlAs alloy surface roughness inducing anisotropy in surface diffusion and/or reactivity at step edges [6,10].…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The luminescence light from the sample was focused with collection lenses, dispersed by a 1.2 m SPEX single grating monochromator and detected by a liquid nitrogen cooled Ge detector. InAlAs have elongated-shape along the [1][2][3][4][5][6][7][8][9][10] direction. This can be attributed to intrinsic InAlAs alloy surface roughness inducing anisotropy in surface diffusion and/or reactivity at step edges [6,10].…”
Section: Methodsmentioning
confidence: 98%
“…For example, a QD laser is expected to have higher gain, lower threshold current density, and higher thermal stability compared with other quantum structures due to the atomic-like density of states in a QD system. However, the superior device performance has not been demonstrated to date mainly due to the difficulties in controlling small QDs at the nanometer scale in terms of both high quality and uniformity, indicating that a number of problems still remain unsolved [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the red-shift in the PL peak position from the reference QD1 sample in this work are mainly due to an increase in a QD size and the low potential barrier of the In 0.15 Ga 0.85 As layer [7,10,11]. It has been previously reported that because the influence of the height fluctuation on the PL linewidth is much larger than that lateral one [9,12], the reduction in the PL linewidth would be expected for the QDs with higher aspect ratio (height/width). And the relatively larger energylevel spacing between the ground states and the first excited states can also be explained by the shape and size of a QD, where the wave-function of QD is more confined in the QD with the high aspect ratio resulting in stronger quantum effects [7,13].…”
Section: Methodsmentioning
confidence: 83%
“…1(b). In our previous work [7], the QD size, especially the QD height, is increased by capping the InAs QDs with the InGaAs overgrowth layer, in which the modification in a QD can be attributed to the local directional migration of Ga and In adatoms around the InAs QD and the suppression of In segregation changing the compositional mixing, because In already exists in the InGaAs layer, when depositing an InGaAs layer on an InAs QD layer [7][8][9]. Therefore, the red-shift in the PL peak position from the reference QD1 sample in this work are mainly due to an increase in a QD size and the low potential barrier of the In 0.15 Ga 0.85 As layer [7,10,11].…”
Section: Methodsmentioning
confidence: 98%
“…So, at the beginning, the height of QDs is hardly affected. Because the ground emission energy is mainly determined by the height of QDs [17,18], no blueshift occurs in the PL peak of QDs. When the annealing temperature is higher, the In/Ga interdiffusion becomes stronger.…”
Section: Methodsmentioning
confidence: 98%